Defining Spotting in Dance: A Delphi Method Study Evaluating Expert Opinions - Haber, Catherine; Schärli, Andrea (Frontiers in Psychology, 2021)
Spotting is a typical isolated head coordination used by many dancers during rotation. However, with sporadic and inconclusive explanations as to why dancers spot, the critical characteristics and functionalities of spotting have yet to be identified. Therefore, a Delphi method survey was used as a novel methodology for providing greater insights into this under-examined motor behavior; bringing together experts from various disciplines to generate ideas and identify the crucial elements of spotting. Following the selection of experts, three rounds of data collection and analysis were conducted to narrow down relevant topics and evaluate consensus. To gather opinions in Round 1, experts were asked to respond freely to three prompts regarding the reasoning, characteristics, and uses of successfully spotting; responses were then grouped into predominant items. To rate agreement in Round 2, experts rated their agreement on the relevance of the grouped items from Round 1 on a 5-point Likert Scale; items rated 4 or 5 by at least 70% of the experts were taken as those consensually relevant to the group. To rank importance in Round 3, Best-Worst Scaling was used to determine individual rankings of the relevant items from Round 2. In a series of comparisons, experts were prompted to select the most and least important items in multiple sub-groupings. Group mean ranking of items as well as ranking concordance and differentiation were analyzed to determine the most important items and the strength of consensus, respectively. Overall, consensus and differentiation in experts’ item rankings were low; however, novel insights were presented. As characteristics of successfully spotting, experts emphasized head isolation, timing, and gaze specificity alongside functional characteristics, substantiating spotting as purposeful action in rotation. Building on traditional notions of spotting for reduced dizziness and maintaining balance, successfully spotting was further deemed useful for multiple turns, orientation, and rhythm. The findings of this study thus provide informed guidelines for future analysis and training of this complex head coordination in rotations.